A critical review on the utilization of various reinforcement modifiers in filled rubber composites. (March 2020) - Roy, Kumarjyoti; Debnath, Subhas Chandra; Potiyaraj, Pranut
Presently, the development of high-performance filled rubber composites offers a new era in the industrial field of polymer research. This article reviews the utilization of various reinforcement modifiers on the successive property enhancement of rubber composites containing different commonly used fillers like silica, nanoclay, carbon nanotube, natural fibers, and so on. The practical importance of reinforcement modifiers in rubber technology is systematically described in the light of filler dispersion, processing, and mechanical properties of filled rubber compounds. A special emphasis is given on the mechanism of interaction between reinforcement modifiers and filler surface in filled rubber composites. Filler dispersion in the rubber matrix is the key parameter that controls the ultimate performance and rubber–filler interaction of filled rubber system. The use of some fixed reinforcement modifiers is an innovative way not only to solve the dispersion problem of filler particles but also to increase the reinforcing ability of most of the fillers in filled rubber products. Thus, the concept of reinforcement modifiers has the potential to facilitate further development of filler reinforcement technology for rubber-based composite materials.